2017
DOI: 10.1111/1462-2920.13719
|View full text |Cite
|
Sign up to set email alerts
|

Divide and conquer: the Pseudomonas aeruginosa two‐component hybrid SagS enables biofilm formation and recalcitrance of biofilm cells to antimicrobial agents via distinct regulatory circuits

Abstract: The opportunistic pathogen Pseudomonas aeruginosa forms antimicrobial resistant biofilms through sequential steps requiring several two-component regulatory systems. The sensor-regulator hybrid SagS plays a central role in biofilm development by enabling the switch from the planktonic to the biofilm mode of growth, and by facilitating the transition of biofilm cells to a highly tolerant state. However, the mechanism by which SagS accomplishes both functions is unknown. SagS harbors a periplasmic sensory HmsP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
70
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(71 citation statements)
references
References 65 publications
(151 reference statements)
1
70
0
Order By: Relevance
“…BrlR is a c-di-GMP responsive transcriptional regulator (35). Previous findings demonstrated BrlR to be absent or detectable at only low levels in total extracts characterized by low c-di-GMP levels, and unable to bind to its target promoters P brlR , P mexA , and P mexE , resulting in significantly increased susceptibility but reduced brlR, mexA, and mexE transcript levels (17,(33)(34)(35)(36). However, BrlR levels and BrlR-DNA binding was restored upon or overexpression of a diguanylate cyclase or the addition of c-di-GMP to the binding assay, respectively (17,35).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…BrlR is a c-di-GMP responsive transcriptional regulator (35). Previous findings demonstrated BrlR to be absent or detectable at only low levels in total extracts characterized by low c-di-GMP levels, and unable to bind to its target promoters P brlR , P mexA , and P mexE , resulting in significantly increased susceptibility but reduced brlR, mexA, and mexE transcript levels (17,(33)(34)(35)(36). However, BrlR levels and BrlR-DNA binding was restored upon or overexpression of a diguanylate cyclase or the addition of c-di-GMP to the binding assay, respectively (17,35).…”
Section: Resultsmentioning
confidence: 99%
“…By analyzing biofilms by P. aeruginosa mutant strains characterized by various intracellular levels of c-di-GMP and strains overexpressing diguanylate cyclases and phosphodiesterases, Gupta et al (17) demonstrated that biofilm cells remain resistant to antimicrobial agents at c-di-GMP levels above 62 pmol/mg but not at or below 40 pmol/mg. These findings suggested a switch in susceptibility in a manner dependent on the c-di-GMP level but independent of the mode of growth or biofilm biomass accumulation (17,33). Moreover, the findings suggested a disconnect between the biofilm architecture and biofilm tolerance (33).…”
mentioning
confidence: 92%
See 3 more Smart Citations